Keperluan pendidikan untuk penyakit buah pinggang kronik - Sowtali, Siti Noorkhairina; Harith, Sakinah; Mohd Shah, Azarisman Shah; Ishak, Nur Ain'; Mohd Yusoff, Dariah; Draman, Che Rosle; Mohd Rasani, Ali Aminuddin; Ghazali, Norhasyimah (2020)
This questionnaire is an output after the closure of RIGS16-143-0307 grant and was developed in a final year project entitled "Educational needs assessment among patients with chronic kidney disease'. It is suitable to be utilized by the healthcare professionals, students and society in general particularly to assess the clients or patients' educational needs related to chronic kidney disease. It consists of seven (7) specific domains of CKD: general information on CKD, management of risk factors CKD, management of complications CKD, medications, self-care management, treatment options and financial status.